(untitled) (Bangladesh Journal of Botany, 2014)
The effects of tanneries wastewater on growth and yield of three cultivars (SF-187, CRN-1435 and DK- 3915) of sunflower (Helianthus annuus L.) showed that wastewater was not fit for irrigation due to extremely high mineral and heavy metal contents. In addition, effluents were highly alkaline with high load in EC, BOD, COD and SAR values. The amount of iron, manganese, zinc and chromium was also quite high. The growth and yield of plants was adversely affected by effluents treatment, especially at higher doses from seedling stage to maturity leading to reduce biomass and seed production as compared to control. Effluents of tanneries used for irrigation purposes proved to be alarmingly toxic to the growth and yield of the important crop in Kasur region, Pakistan. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18030 Bangladesh J. Bot. 42(2): 279-285, 2013 (December)